Student-centred, lecturer-centred, and hybrid teaching methods: Impacts on accounting students' technical and soft skills - Sulaiman, Noor Adwa; Shahimi, Suhaily; Zakaria, Zarina (Asian Journal of Accounting Perspectives, 2021)
Research aim: This study examines the impacts of teaching methods: student-centred, lecture-centred, and hybrid (lecture-student) on technical and soft skills of accounting students. Design/ Methodology/ Approach: The impacts are assessed via a structural modelling procedure using Smart PLS based on survey data gathered from accounting students in one public university in Malaysia. Research findings: Results show the lecturer-centred method impacting the students’ technical skills, and the hybrid method impacting students’ technical and soft skills. It is evident from the analysis that there is minimal impact of the student-centred teaching method on technical and soft skills and of the lecturer-centred teaching method on soft skills of the accounting students. The results suggest that the hybrid teaching method is the most effective teaching method in enhancing accounting students’ technical and soft skills. Practitioner/ Policy implication: This research could assist universities and policymakers to formulate relevant teaching strategies and approaches to enhance accounting students’ competency. Limitation/ Implication: The findings in this study is revisiting and revising the current teaching methods is necessary to prepare future accountants for a career in accounting. Keywords: Accounting Students, Soft Skills, Teaching Methods, Technical Skills Type of manuscript: Research paper JEL Classification: M41, M42, M48, L84